EVALUATION OF ANTIBIOTIC USE FOR DIARRHEA THERAPY IN TODDLERS AT PUSKESMAS BEJI DEPOK CITY - Masyithah, Lathvi; Rosmawati, Rosmawati; Suzana, Dona (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2025)
Acute diarrhea is diarrhea more than fourteen days and is generally caused by microbial infection. The principles management of acute diarrhea are rehydration, symptomatic therapy, and selective and rational antibiotic therapy. Previous study shown antibiotic prescriptions for diarrhea therapy are still quite high, a study at the Bangsal Puskesmas in Mojokerto Regency showed that 27% was inappropriate for the indication. The aim this study was to evaluate the rationality of using antibiotics for diarrhea in toddlers. This study is a descriptive study with retrospective data collection from the medical records of toddler diarrhea patients at the Puskesmas Beji in Depok City in 2021 who met the inclusion and exclusion criteria. The results of the study showed the use of antibiotics such as metronidazole, amoxicillin, and cotrimoxazole was the right choice because it was in accordance with the choice of antibiotic therapy for acute diarrhea with specific indications, however the results of the evaluation of antibiotic prescriptions were not appropriate indications there was still a high number 62,5% of antibiotic prescriptions for patients with non-specific acute diarrhea. Antibiotic prescriptions must be based on the bacteria causing the infection so it is very necessary to be supported by data from laboratory tests.